Counseling Regarding Knowledge and Attitudes on Pre Marriage Sex to Teenagers in High Schools In The DKI Jakarta Region Using The LeafLets Method - Putri Azzahroh; Azizah, Nurul; Silawati, Vivi (Rajaki of Tulip Medika Publisher, 2024)
Background: the impact of premarital sex in the modern era does not only impact the individual concerned, but directly or indirectly also impacts society and the surrounding environment. The impact of premarital sex is the risk of suffering from sexually transmitted diseases, unwanted pregnancies, psychological trauma, giving birth to unhealthy babies, disgrace to the family, increasing teenagers dropping out of school and increasing maternal and infant mortality rates so that the level of public health decreases. Objective: Carry out community service activities by carrying out activities ranging from collecting secondary data to conducting interventions and evaluating field activities. Method: This research consists of education regarding information, knowledge and attitudes of premarital sex. Results: After being given education to increase knowledge and attitudes regarding premarital reproductive health, the students felt satisfied and committed to preventing them from falling into promiscuous sexual behavior, because they knew the dangers and impacts that could occur from premarital sex. Conclusion: This research include obtaining activity permits, providing education regarding Premarital Reproductive Health, providing videos related to educational materials, and providing souvenirs. Community service activities run smoothly.